Klasycy rosyjscy wobec konfliktu bałkańskiego 1875–1878 - Żejmo, Bożena (Studia Rossica Posnaniensia, 2015)
The national liberation struggle of the southern Slavic peoples in the second half of the 19th century attracted the attention of Russian society, including writers. The Slavic question and especially the Russo-Turkish War inspired both writers and journalists to reflect on the cardinal problems of the development of Russia itself. The Slavic question turned into the Russian question.